The effects of 6-week silat specific intervention on technical and tactical aspects of silat olahraga athletes / Siti Jameelah Md Japilus - Md Japilus, Siti Jameelah (2014)
Background and purpose of study: The objective of this present study is to identify the effectiveness of 6-weeks silat-specific intervention on technical and tactical aspects in silatolahraga. Protocols: 20 male participants aged from 18-25 year-old, universities silatolahraga athletes who have less than 6 month experienced in silatolahraga were assigned into two groups, intervention group (n=10) and control group (n=10) after underwent pre-intervention match on the beginning of data collection. Both groups follow two different training interventions which intervention group followed silat-specific intervention while control group followed conventional silat training for 6-weeks. Pre and post-sparring match was done through video records and analysed by hand notational analysis.